Nzema Idiomatic Expressions as Indirection Strategy: A Politeness Theoretical Perspective - John Nyame; Kwasi Adomako; Mohammed Yakub; Rahinatu Taiba Ibrahim; Esther Nana Anima Wiafe-Akenten (Universitas Sanata Dharma, 2023)
The paper explores Nzema idiomatic expressions used as indirection strategy. Figurative devices such as proverbs and euphemisms have received quite an appreciable amount of study in connection with verbal indirection in Nzema. Little or no attention however has been given to idioms, particularly as indirection devices in the language. This paper therefore focuses on idioms which incorporate body parts such as head/brain, eyes, nose, mouth, teeth, hands, legs, heart/chest, stomach and body/skin that are used to avoid any straightforward language that seeks to undermine and threaten the face of an addressee. Data were gathered from both primary and secondary sources. The primary data comprise recordings of traditional ceremonies such as marriage contraction and arbitration, where the use of idioms as indirect expressions was pervasive. Authors’ native speaker intuition was also brought to bear on the analysis of data. Interviews with competent indigenous speakers of Nzema were conducted for useful information and clarification on the data gathered. The secondary data were sourced from two Nzema literary texts. The paper finds that, these culturally constructed body parts related idioms are deliberately employed as both face saving and as politeness devices in the language.